Study of the Segmental Dynamics and Ion Transport of Solid Polymer Electrolytes in the Semi-crystalline State - Chen, Xi Chelsea; Sacci, Robert L.; Osti, Naresh C.; Tyagi, Madhusudan; Wang, Yangyang; Keum, Jong K.; Dudney, Nancy J. (Frontiers in Chemistry, 2021)
Solid polymer electrolytes are promising in fulfilling the requirements for a stable lithium metal anode towards higher energy and power densities. In this work, we investigate the segmental dynamics, ionic conductivity, and crystallinity of a polymer electrolyte consisting of PEO and lithium triflate salt, in the semi-crystalline state. Using quasi-elastic neutron scattering, the segmental dynamics of PEO chains confined between the crystalline lamellae is quantified, using Cole-Cole analysis. We show that the structural relaxation time, τ0, of PEO equilibrated near room temperature is 6-fold longer than the same sample that had just cooled down to room temperature. This corresponds to a 3-fold smaller ionic conductivity in the equilibrated condition. This work reveals that the segmental dynamics of semi-crystalline polymer electrolytes is very sensitive thermal history. We demonstrate that quasi-elastic neutron scattering can be used to characterize the ion transport and segmental dynamics in the semi-crystalline state.